Tribological studies on bearing balls of different composition using certain heterocyclic compounds as potential E.P. Additives - Singh T.; Verma V.K. (My University, 2025)
Tribological studies on 12.7 mm dia steel bearing ball specimens of different composition have been carried out in a “4-ball machine” using certain potentially active heterocyclic compounds-paraffin oil admixtures. EP efficiency of these additives has been compared to a commercial sulphur-phosphorus additive. 2-Phenyl-3-phenylimino- 5-p-methoxyphenylimino-l,2,4-thiadiazolidine has been found to be quite effective in the lubrication of bearing balls of different compositions. The topography and surface chemistry of the used bearing ball specimens have been examined using Scanning Electron Microscopy and Scanning Auger Electron Spectroscopy techniques respectively. Employing a suitable additive, the costlier alloy steel balls can be replaced by cheaper low carbon and chromium balls. © 1990 by ASME.